Do Not‐For‐Profits Need Their Own Conceptual Framework?. (November 2014) - Ryan, Christine; Mack, Janet; Tooley, Stuart; Irvine, Helen
Abstract This paper raises the issue of whether not‐for‐profit (NFP) oganisations require a conceptual framework that acknowledges their mission imperative and enables them to discharge their broader accountability. Relying on publicly available documentation and literature, it suggests the current Conceptual Frameworks for the for‐profit and public sectors are inadequate in meeting the accountability needs of NFPs. A NFP‐specific conceptual framework would allow the demonstration of broader NFP‐specific accountability and the formulation of NFP‐appropriate reporting practice, including the provision of financial and non‐financial reporting. The paper thus theoretically challenges existing financial reporting arrangements and invites debate on their future direction.